Combination of NKT14m and Low Dose IL-12 Promotes Invariant Natural Killer T Cell IFN-γ Production and Tumor Control - Guan, Peng (Int J Mol Sci, 2020)
Invariant natural killer T (iNKT) cells are innate-like T lymphocytes characterized by the expression of an invariant T cell receptor (iTCR) that recognizes glycolipid antigens presented by the MHC I-like CD1d molecule. Following antigenic stimulation, iNKT cells rapidly produce large amounts of cytokines that can trans-activate dendritic cells (DC) and promote the anti-tumor functions of cytotoxic lymphocytes, such as natural killer (NK) and CD8 T cells. Additionally, iNKT cells can mediate robust and direct cytotoxicity against CD1d(+) tumor targets. However, many tumors down-regulate CD1d and evade iNKT cell attack. To circumvent this critical barrier to iNKT cell anti-tumor activity, a novel monoclonal antibody (mAb), NKT14 has been recently developed. This agonistic antibody binds directly and specifically to the iTCR of murine iNKT cells. In the current study, we demonstrate that NKT14m mediates robust activation, cytokine production and degranulation of murine iNKT cells, in vitro. Consistently, NKT14m also promoted iNKT cell activation and immunomodulatory functions, in vivo. Finally, administration of NKT14m with low dose interleukin (IL)-12 further augmented iNKT cell IFN-γ production in vivo, and this combination conferred superior suppression of tumor cell growth compared to NKT14m or IL-12 alone. Together, these data demonstrate that a combination treatment consisting of low dose IL-12 and iTCR-specific mAb may be an attractive alternative to activate iNKT cell anti-tumor functions.